KARAKTERISTIK MESIN HONDA JAZZ 2007 I-DSI - Jusnita; Fithry, Dwi Annisa; Azizi, Farux (Fakultas Teknik UMRI, 2022)
Electrinic Fuel Injection (EFI) a system that supplies fuel from the tank electronically with a mixture of air that suits fuel needs so that vehicle power remains maximum with minimal fuel consumption to produce environmentally friendly emissions. The fuel injection system is an innovation step that is being developed and applied to motor vehicles today. The purpose of the study was to find out the characteristics of the 2007 Honda Jazz I-DSI engine using the parameters of maximum torque, maximum power, average effective pressure (Brake Mean Effective Pressure) and specific fuel consumption (Specific Fuel Consumption). The method used is direct observation of the problems related to this study. Torque as the rotation of the Honda Jazz i-DSI engine shaft has a higher torque. This shows that the Honda Jazz engine has a higher torque value to improve engine performance. Effective engine power occurs at engine shaft revolutions of 1000 to 5000 rpm. The specific fuel consumption of the Honda Jazz engine has a higher specific fuel consumption value of 34.23% than the i-DSI with the PGM-FI (Programmed Fuel Injection) fuel supply system. At 3500 to 6000 rpm, the Honda Jazz i-DSI engine has a higher specific fuel consumption value compared to the PGM-FI fuel supply system. So the use of fuel using the i-DSI engine is more efficient at low revs because it uses 2 spark plugs, so combustion can be maximized. The thermis efficiency of the Honda Jazz i-DSI engine has a higher thermis efficiency value of 11.15%. Thermis efficiency rises when the engine revs up. Then it can be said that the efficiency of the thermis is directly proportional to the rotation of the engine.